Gain of 1q21 is an adverse prognostic factor for multiple myeloma patients treated by autologous stem cell transplantation: A multicenter study in China. (2nd September 2020) - Gao, Wen; Jian, Yuan; Du, Juan; Li, Xiaozhe; Zhou, Huixing; Zhang, Zhiyao; Yang, Guangzhong; Wang, Guorong; Tian, Ying; Li, Yanchen; Wu, Yin; Fu, Weijun; et al.
Abstract: Background: Autologous stem cell transplantation (ASCT) has been recommended as a standard approach for young multiple myeloma (MM) patients for decades, even in the era of novel agents. Gain of chromosome 1q21 is a common cytogenetic abnormality in MM, while its clinical prognostic value is still controversial. Methods: In this multicenter study, we retrospectively analyzed 1q21 gain in 446 newly diagnosed MM patients who received at least one ASCT from three large myeloma centers in China. Results: Of the all 446 patients, 1q21 gain was an adverse predictor of progression‐free survival (PFS) (34 vs 56 months, P = .005) and overall survival (OS) (69 vs 100 months, P = .002). Gain of 1q21 was more likely to coexist with t(4;14), t(14;16), and del(13q). Nevertheless, isolated 1q21 gain still exhibited unfavorable effects on PFS (35 vs 66 months, P = .045) and OS (61 vs 100 months, P = .026). The coexistence of 1q21 gain and high‐risk cytogenetics (HRCs) [del(17p), t(4;14), and/or t(14;16)] showed poor prognosis on both PFS and OS, while no additional adverse effect could be identified when compared with HRCs alone. Moreover, when coexisting with t(11;14), patients with 1q21 gain showed a comparable survival to those without 1q21 gain. For patients treated with novel induction regimens followed by ASCT, 1q21 gain also conferred an inferior prognosis. Multivariate analysis further confirmed 1q21 gain could independently predict shorter PFS and OS. Conclusion: In conclusion, 1q21 gain is an adverse prognostic factor for MM patients received ASCT. Abstract : Gain of 1q21 is an independent adverse prognostic factor in MM patients receiving ASCT in the era of novel agents. Isolated 1q21 gain still showed adverse impact on patient's survival.